To research online or not to research online: using internet-based research in Islamic Studies context - Nurdin Nurdin (Indonesian Journal of Islam and Muslim Societies, 2017)
" Indonesia is the largest Muslim country and the eighth largest Internet user in the world. Around 78 million people in Indonesia use the Internet in their daily lives. This provides new opportunities for Islamic education institutions and Muslim scholars to utilise this online space as a new research setting. Non-Islamic education institutions and scholars have utilised the Internet as a new avenue to conduct research, while Islamic education institutions and Muslim scholars have yet to make use of online space for research purposes.While dakwah, education and other Islamic social phenomena are being practiced on online platforms, Muslim scholars are yet to go online to understand this phenomenon. This paper addresses why Islamic institutions and Muslim scholars should go online and utilise the Internet as a new setting in their research agenda. This paper offers researchers at Islamic institutions the opportunity to consider new data collection and triangulation strategies to enhance their research output and paradigm. The paper’s discussion focuses on both quantitative and qualitative research methods. Some benefits of using social media in a research setting are discussed. Evidence that supports researchers utilising social media for research purposes are also summarised.Future research needs to focus on the application of this idea in empirical contexts, as well as consider ethical issues.Indonesia merupakan salah satu negara dengan penduduk Muslim terbesar didunia and pengguna Internet kedelapan besar didunia. Saat ini ada sekitar 78 juta penduduk Indonesia menggunakan Internet dalam keseharian mereka. Fakta ini menjadi peluang baru bagi lembaga pendidikan Islam dan para ahli Muslim untuk memanfaatkan sarana online tersebut sebagai salah satu tempat penelitian baru. Lembaga pendidikan umum dan para ahli non-Muslim telah lama memanfaatkan sara online tersebut untuk kepentingan penelitian mereka, sementara lambaga pendidikan Islam dan para pakar Muslim masih belum juga memanfaatkan peluang baru ini. Padahal sejumlah fenomena ke-Islaman sudah di praktekkan di dunia online seperti Dakwah, pendidikan, dan berbagai aktifitas sosial ke-Islaman lainnya. Tulisan ini mengkaji mengapa lembaga pendidikan Islam dan para ahli Muslim sudah harus merubah paradigma penelitian mereka dengan beralih ke dunia online sebagai tempat baru untuk melakukan penelitian. Tulisan ini menyimpulkan agar lembaga pendidikan Islam dan para ahli Muslim untuk mempertimbangkan strategi baru dalampengumpulan data dan trianggulasi guna memperkaya hasil dan paradigma penelitian baik untuk penelitian kualitatif maupun kuantitatif. Tulisan ini juga menyajikan sejumlah keuntungan dari pemanfaatan dunia online sebagai karena baru penelitian. Sejumlah argumen dan contoh-contoh juga disajikan guna memperkuat hasil penelitian ini. Tulisan ini juga menyarankan agar kedepan ada penelitian lain yang menggunakan data empiris terkait perlunyapemanfaatan dunia online dalam penelitian terkait Islam.